Développement du sentiment d’efficacité personnelle perçu par des enseignantes œuvrant auprès d’élèves ayant un trouble du spectre de l’autisme au secondaire et appropriation de nouvelles pratiques évaluatives - Lamarche, Marie-Aimée; Durand, Micheline-Joanne (Canadian Journal of Education/Revue canadienne de l’éducation, 2022)
Assessing students with an autism spectrum disorder (ASD) is a constant challenge. It impacts the sense of personal effectiveness of teachers working with these learners who can have multiple specificities and for whom adjustments to pedagogical practices, and specifically assessment practices, are often essential. According to the literature, teachers’ self-efficacy has a direct effect on teaching practices and their mental health. The results of our study suggest that the appropriation of practices can improve teachers’ self-efficacy when they are involved in a professional development process providing suitable material and support.